Low back pain and domestic activities in women treated at a rehabilitation center in Lima: Dolor lumbar y actividades domésticas en mujeres atendidas en un centro de rehabilitación de Lima - Barreda-Castillo, Evelyn Liliana (2019)
Objective: To determine the relationship between low back pain and domestic activities in women treated in a rehabilitation center. Material and Methods: Descriptive cross-sectional and correlational study. The sample consisted of 200 women housewives attended in a private rehabilitation center. A validated questionnaire was used, with a reliability of 0.71 (Crombach's alpha). To evaluate the state of anxiety, the Goldberg Test or EADG was used. Results: Low back pain was associated with instruction level, age, occupation of housewife, sitting posture, walking posture, ironing, cleaning, load or transfer, depression (p < 0.001), children under six years (p = 0.037) and anxiety ( p = 0.004). Conclusion: domestic activities influence the development of low back pain, which can cause functional limitation in their domestic activities and their quality of life of housewives. Keywords: Lumbar Region Pain; Women, Rehabilitation Centers (Source: MeSH, NLM).